Analisis Kebutuhan Media E-Picture Story Book untuk Siswa Kelas IV Sekolah Dasar - Muntamah Muntamah; Ali Mustadi; Fery Muhammad Firdaus (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The low reading literacy of grade IV elementary school students is a challenge that needs to be overcome by teachers. The absence of learning media that is in accordance with the characteristics and needs of students is one of the factors causing low reading literacy in grade IV elementary school students. This study aims to analyze the needs of teachers and grade IV elementary school students for e-picture story book media. This study uses a qualitative descriptive approach with data collection techniques through teacher interviews, student needs questionnaires, and observation. The study was conducted in March 2025 with research subjects of grade IV elementary school students in Kombel 2 Kapanewon Depok, Sleman Regency, Special Region of Yogyakarta. The results of the study showed that the learning media used were not yet varied. Teachers still use makeshift textbooks at school, so they are less interesting for students to read. In addition, technology-based learning media such as e-picture story book media have not been used. So teachers and students want to develop learning media according to the characteristics and learning needs of students.